Internal Control Weakness and Bank Loan Contracting: Evidence from SOX Section 404 Disclosures - Kim, Jeong-Bon; Song, Byron Y.; Zhang, Liandong (The Accounting Review, 2011)
ABSTRACT Using a sample of borrowing firms that disclosed internal control weaknesses (ICW) under Section 404 of the Sarbanes-Oxley Act, this study compares various features of loan contracts between firms with ICW and those without ICW. Our results show the following. First, the loan spread is higher for ICW firms than for non-ICW firms by about 28 basis points, after controlling for other known determinants of loan contract terms. Second, firms with more severe, company-level ICW pay significantly higher loan rates than those with less severe, account-level ICW. Third, lenders impose tighter nonprice terms on firms with ICW than on those without ICW. Fourth, fewer lenders are attracted to loan contracts involving firms with ICW. Finally, our within-firm analyses show that banks increase loan rates charged to ICW firms after their disclosure of internal control problems and that banks reduce loan rates after firms remediate previously reported ICW.